2012
DOI: 10.1016/j.neuron.2012.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Visual Attention and Episodic Retrieval: Dissociable Contributions of Parietal Regions during Gist-Based False Recognition

Abstract: SUMMARY The interaction between episodic retrieval and visual attention is relatively unexplored. Given that systems mediating attention and episodic memory appear to be segregated, and perhaps even in competition, it is unclear how visual attention is recruited during episodic retrieval. We investigated the recruitment of visual attention during the suppression of gist-based false recognition, the tendency to falsely recognize items that are similar to previously encountered items. Recruitment of visual atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 51 publications
3
42
0
Order By: Relevance
“…Like the anterior hippocampus, the inferior parietal lobule has been implicated in studies in which participants imagine events in more specific (vs. more general) detail (19), particularly during the construction phase (21). The inferior parietal lobule is also part of the MTL subsystem that is thought to track with episodic memory, event imagination, and scene content (15), and activity in this region has been associated with the successful retrieval and integration of perceptual details from memory (20). In a related topic, we found evidence that activity in the right ventral precuneus increased following the specificity induction relative to the control for imagined events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like the anterior hippocampus, the inferior parietal lobule has been implicated in studies in which participants imagine events in more specific (vs. more general) detail (19), particularly during the construction phase (21). The inferior parietal lobule is also part of the MTL subsystem that is thought to track with episodic memory, event imagination, and scene content (15), and activity in this region has been associated with the successful retrieval and integration of perceptual details from memory (20). In a related topic, we found evidence that activity in the right ventral precuneus increased following the specificity induction relative to the control for imagined events.…”
Section: Discussionmentioning
confidence: 99%
“…In light of our behavioral characterization of the specificity induction, we hypothesize and test here that (i) this induction should impact primarily structures within the MTL subsystem, in particular those regions-the hippocampus and inferior parietal lobule-that have been linked previously to detailed episodic retrieval and to imagining of specific (vs. general) future events (18)(19)(20). Moreover, our behavioral characterization of the specificity induction as affecting primarily participants' retrieval orientation when they construct mental events or scenes leads us to predict that (ii) these effects will be observed mainly during the initial construction of an event.…”
Section: Significancementioning
confidence: 99%
“…First, variance adaptation may depend on high-level representations in the ventral stream that have extracted abstract, correlated structure throughout visual development, and come to represent the variance in a fashion untied to the specific input (42). Second, variance adaptation may depend on dorsal stream structures that are conjectured to support gist-based retrieval (43) and are involved in controlling covert attention and saccadic exploration of a scene (44). We hope that future research will arbitrate among these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in these experiments typically classify the old items as 'old' much more frequently than they classify the new, unrelated items as 'old', which constitutes evidence for true or veridical memory. The critical result is that participants also classify new, related items as 'old' much more frequently than new, unrelated items; these incorrect responses to the related items constitute evidence for false memories (e.g., [24][25][26][27] ). Other neuroimaging studies have examined false memories that result from confusing perception and imagination 28,29 .…”
Section: Distinguishing True and False Memories With Neuroimagingmentioning
confidence: 99%
“…For example, several studies have reported that brain regions involved in encoding or retrieving sensory-perceptual information tend to be more active during retrieval of true than false memories (e.g., [24][25][26][27]29,32 ).…”
Section: Distinguishing True and False Memories With Neuroimagingmentioning
confidence: 99%